Isolated Gait Ataxia as a Sole Manifestation of Right Lateral Medullary Infarct following Ipsilateral Trigeminal Herpes Zoster - Seung-Jae Lee; Dong-Geun Lee (Case Reports in Neurology, 2014)
Background: Cerebral infarct related to varicella-zoster virus (VZV) has been reported in the literature. In addition, lateral medullary infarct (LMI) can be manifested rarely as isolated gait ataxia without other characteristic symptoms. Case Report: A 70-year-old female was admitted to our hospital because of herpes zoster on the right trigeminal nerve distribution. On the 15th hospital day, she developed sudden vertigo and fine left-beating nystagmus with axial lateropulsion to the right side, without the other usual signs of LMI (Horner syndrome, dysarthria, swallowing difficulty or hemibody sensory change). Brain MRI showed a small infarct in the far dorsolateral portion of the right rostral medulla and pontomedullary junction. Cerebrospinal fluid study showed a positive VZV IgG antibody. Conclusions: We reported a case of isolated gait ataxia as the sole manifestation of right LMI following herpes zoster on the right trigeminal distribution. A high index of clinical suspicion for concomitant central nervous system complication is necessary in patients with herpes zoster, although the concomitant neurologic symptom may be mild or less lateralized.